2014
DOI: 10.1186/s12983-014-0090-9
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dynamics of myogenesis in the shipworm Lyrodus pedicellatus (Mollusca: Bivalvia)

Abstract: BackgroundThe shipworm Lyrodus pedicellatus is a wood-boring bivalve with an unusual vermiform body. Although its larvae are brooded, they retain the general appearance of a typical bivalve veliger-type larva. Here, we describe myogenesis of L. pedicellatus revealed by filamentous actin labelling and discuss the data in a comparative framework in order to test for homologous structures that might be part of the bivalve (larval) muscular ground pattern.ResultsFive major muscle systems were identified: a velum r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…2B, B 0 ). This muscle topologically corresponds to the anlage of the pedal plexus in Lyrodus pedicellatus (Wurzinger-Mayer et al, 2014). At 48 hpf, another muscle is newly detected at the posterior end of the ventral larval retractor.…”
Section: Results Early Development Of S Virgatusmentioning
confidence: 89%
See 2 more Smart Citations
“…2B, B 0 ). This muscle topologically corresponds to the anlage of the pedal plexus in Lyrodus pedicellatus (Wurzinger-Mayer et al, 2014). At 48 hpf, another muscle is newly detected at the posterior end of the ventral larval retractor.…”
Section: Results Early Development Of S Virgatusmentioning
confidence: 89%
“…Since the description of the early development of Cerastoderma edule (Heterodonta: Cardiidae), the embryology of bivalves has been studied using microscopic observation and immunochemistry (Lov en, 1848;Hatschek, 1880;Meisenheimer, 1901;Cole, 1938;Creek, 1960;Allen, 1961;Cragg, 1985;Kakoi et al, 2008;Dyachuk & Odintsova, 2009;Wurzinger-Mayer et al, 2014). A classical microscopic study by Lillie (1895) reported that the adductor muscles, as well as the larval retractor muscles, of the freshwater clam Lasmigona complanata (Palaeoheterodonta: Unionidae) develop from ectomesoderm cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…kogamogai but also in other gastropods, bivalves, polyplacophorans, solenogastres, and caudofoveates as well as in annelids and entoprocts (e.g. Page 2002b; Wanninger and Haszprunar 2002a;Nielsen et al 2007;Wollesen et al 2008;Dyachuk and Odintsova 2009;Evans et al 2009;Wanninger 2009;Page and Ferguson 2013;Scherholz et al 2013;Wurzinger-Mayer et al 2014;Merkel et al 2015). The absence of such a prototrochal muscle ring in Scaphopoda suggests, once again, a secondary loss (Wanninger and Haszprunar 2002b).…”
Section: Neuromuscular Patterns In Gastropoda and Other Molluscsmentioning
confidence: 99%
“…Bivalve and gastropod larvae show striking similarities in their larval musculature such as the velum retractor muscles and the prototroch or velum muscle ring. In general, the larval retractor muscles are striated, insert posteriorly at the inner shell, project into the velum, foot or mantle, and in almost all cases degenerate during metamorphosis (Degnan et al 1997;Page 1998;Wanninger et al 1999a;Wollesen et al 2008;Dyachuk and Odintsova 2009;Kristof and Klussmann-Kolb 2010;Page and Ferguson 2013;Wurzinger-Mayer et al 2014). The muscle ring that underlies the prototroch or velum is not only found in the patellogastropod L. cf.…”
Section: Neuromuscular Patterns In Gastropoda and Other Molluscsmentioning
confidence: 99%